Design of ultra‐thin closely spaced dual‐band bandpass frequency selective surface. Issue 24 (1st November 2017) - Yang, Shilin; Chen, Qiang; Bai, Jiajun; Fu, Yunqi
Abstract : An ultra‐thin compact frequency selective surface with dual passband, which can be independently tuned, has been designed. It produces two passbands at 8.2 and 11.4 GHz with transmission zeros on both sides of the passband to improve frequency selectivity. The electromagnetic coupling structure makes the overall structure ultra‐thin, and the single‐ended short resonator reduces the unit size. Simulation was performed to demonstrate the effectiveness of the design.